Pengaruh Rekrutmen, Pelatihan Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Di Pt Sinar Mandiri Semesta (Tara Hotel Yogyakarta) - Jiman Budiharja; Handy Aribowo; Aloysius Jondar (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
The purpose of this study was to determine whether the recruitment process, training, and job satisfaction and determine which of the three independent variables have the most effect on employee performance. The procedure used in data collection uses a survey method, distributing questionnaires through Google Forms. While data analysis is done through SPSS and Annova software testing. The results showed that (1) recruitment has a positive and significant effect on employee performance based on the t value of the recruitment variable (X1) is 2.279 and the t table value is 1.692. The magnitude of the influence of recruitment (X1) on employee performance (Y) is 0.353, which means that every time there is recruitment (X1), it will increase employee performance (Y) by 0.353 units, (2) training has a positive and significant effect on employee performance based on the t value of the training variable (X2) is 1.935 and the t table value is 1.692. The magnitude of the effect of training (X2) on employee performance (Y) is 0.217, which means that every time there is training (X2), it will increase employee performance (Y) by 0.217 units, (3) job satisfaction has a positive and significant effect on employee performance based on the t value of the satisfaction variable (X3) is 6.548 and the t table value is 1.692. The magnitude of the effect of satisfaction (X3) on employee performance (Y) is 0.678, which means that every time there is satisfaction (X3), it will increase employee performance (Y) by 0.678 units, (4) job satisfaction (X3) is the most influential variable on employee performance seen from the t-test value and multiple linear regression.